Influence of Models Discovery Learning to Critical Thinking Ability and Scientific Attitude of Students - Sri Nursakinah; Suyanta Suyanta (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine critical thinking skills and scientific attitudes, determine students critical thinking skills, determine attitudes scientific, know the effectiveness of the discovery learning model to students' critical thinking skills and scientific attitudes and know the comparison of scientific attitudes. This research is included in the type of quasi-experimental research. The research design used was a posttest only design. The population in this study were all students in class XI IPA in Senior High School. The sample in this study were students of class XI IPA at SMAN 1 Selong. The research sample was taken by random sampling to class. The research instruments used were critical thinking ability questions, scientific attitude used questionnaires and observation sheets. The results of the research show that there are differences in the ability to think critically and the scientific attitude, there is a differen in the ability to think critically, there is a difference in scientific attitudes, the percentage contribution of model to student' critical thinking ability and scientific attitude 31.9%, critical thinking ability 26.1% and scientific attitude 6.7%, scientific attitude profile of discovery learning model is better than 5M scientific approach